THE EFFECT OF THE USE OF ARTIFICIAL INTELLIGENCE-BASED LEARNING APPLICATIONS AND STUDENT ENGAGEMENT ON CREATIVE THINKING SKILLS AT MADRASAH ALIYAH NEGERI 2 PEKANBARU: AI-Based Learning Application, Student Engagement, Creative Thinking Skills - Bahari Pratama Bahari; Risnawati; Zaitun (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the influence of artificial intelligence-based learning applications and student engagement on students' creative thinking skills in the Al-Qur'an Hadith subject at Madrasah Aliyah Negeri 2 Pekanbaru, both partially and simultaneously. This study employed a quantitative approach with a quasi-experimental design using a pretest-posttest control group, involving an experimental group that utilized AI-based learning applications and a control group that relied on conventional textbooks. Data were collected through written tests to measure students' creative thinking skills and structured questionnaires to assess student engagement levels. The data were analyzed using the Independent Sample t-test and Two-Way ANOVA, with prerequisite tests including the Shapiro-Wilk normality test, Levene's Test for homogeneity of variance, and instrument validity and reliability testing. The results revealed that the use of AI-based learning applications had a significant effect on students' creative thinking skills, with a significance value of 0.000, a Mean Difference of 14.40 points, and a Partial Eta Squared of 0.339, which is classified as a large effect. Student engagement also demonstrated a significant effect, with a significance value of 0.000, a Mean Difference of 7.30 points, and a Partial Eta Squared of 0.296, likewise categorized as a large effect. Simultaneously, both variables accounted for 77.9% of the variance in students' creative thinking skills, as indicated by an R Squared value of 0.779. This study concludes that the synergy between AI-based learning applications and student engagement constitutes a proven and effective combination for enhancing students' creative thinking skills in a madrasah environment, while also making a meaningful contribution to the achievement of SDG 4 on quality education.